Transparent and Flexible Thin Film Electroluminescent Devices Using HiTUS Deposition and Laser Processing Fabrication - Costas Tsakonas; Steve Wakeham; Wayne M. Cranton; Mike Thwaites; Gabriel Boutaud; Carly Farrow; Demosthenes C. Koutsogeorgis; Robert Ranson (IEEE Journal of the Electron Devices Society, 2016)
Highly transparent thin film electroluminescent structures offering excellent switch on characteristics, high luminance and large break-down voltages have been deposited onto glass and flexible polymeric materials with no substrate heating using high target utilization sputtering. Deposition of ZnS:Mn as the active light emitting layer and Y2O3, Al2O3, Ta2O5, and HfO2 as dielectric materials arranged in single and multiple layer configurations were investigated. Devices incorporating Al2O3, HfO2 quadruple layers demonstrate the highest attainable luminance at low threshold voltage. Single pulse excimer laser irradiation of the phosphor layer prior to deposition of the top dielectric layer enhanced the luminance of the devices. The devices fabricated on glass and polymeric substrates exhibited a maximum luminance of 500 and 450 cdm-2 when driven at 270 VRMS and 220 VRMS, respectively, with a 1.0 kHz sine wave.